2014
DOI: 10.1002/pts.2084
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Dynamic Properties of Non-linear Packaging Materials Using a Reverse Multiple Input/Single Output Based Approach

Abstract: During the distribution phase, packaged consignments are exposed to a variety of environmental hazards (such as vibrations) that, if excessively severe, may cause damage to or even destroy the product. Structural deterioration can be tracked by monitoring variations in the packaging system's modal parameters, particularly its natural frequency (stiffness). Natural frequency estimates are often extracted using a least‐squares regression curve fit, applied to an estimate of the system's frequency response functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…As shown in Figure 11, the data are the impact velocity V s and the acceleration waveform, from which we can obtain the peak acceleration € According to Equation 4, values of ω n t and V t for the target freefall height are required when predicting € x max t . The value of V t can be obtained from h t of the target free-fall height using Equation 6, and we assume that ω n t is the average of ω n s values.…”
Section: Ls Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 11, the data are the impact velocity V s and the acceleration waveform, from which we can obtain the peak acceleration € According to Equation 4, values of ω n t and V t for the target freefall height are required when predicting € x max t . The value of V t can be obtained from h t of the target free-fall height using Equation 6, and we assume that ω n t is the average of ω n s values.…”
Section: Ls Modelmentioning
confidence: 99%
“…In this study, the regression equation was led as ω dt = − 20.265V i + 263.78, and so ω dt values can be calculated to substitute V i for V t at the target free-fall height in this equation. V t , which is the impact velocity of the target free-fall height, can be determined using Equation 6. The target free-fall height was defined as 60, 70 and 80 cm.…”
Section: Fvd Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work has previously been carried out by the authors towards the development of a post‐processing technique that can determine the condition of packaging samples as a function of time. Various techniques have been developed, most of which make use of the overall system's FRF to extract continuous estimates of the system's natural frequency, which are in turn used as a quantifiable measure of damage (loss in stiffness).…”
Section: Introductionmentioning
confidence: 99%
“…Garcia‐Romeu‐Martinez et al , Rouillard et al and Lamb, showed that the least squares regression technique can be suitable for extracting modal estimates from physical packaging systems. However, for the evaluation of non‐linear systems, the approach is limited to extracting relative estimates (pre and post damage) and to tests, which use a constant excitation level . The authors introduced a non‐linear analysis technique, which separates the linear component of the system's FRF using an optimised reverse multiple input/single output (RMISO) algorithm.…”
Section: Introductionmentioning
confidence: 99%